The Accounting System of Bulgaria and Presentation of Non-Current Assets – Historical Retrospection - Savova, Kameliya (Research Papers, 2023)
The study presents opinions on the nature of the accounting system. The objective connection of the accounting system with the economic reality differentiates its functioning model. In the historical development of Bulgaria, three models of the accounting system have been formed. The study presents the creation of accounting information on non-current assets in the period after the Liberation until today in a methodological aspect. The economic operations for their acquisition, depreciation, sale, restoration, maintenance and operation are considered. A comparative analysis was made with the current methodology for accounting of non-current assets, according to the National Accounting Standards. The result is established similarities and partial differences in the applied approaches in the accounting interpretation of non-current assets of the enterprise.
Keywords: Non-current assets; Accounting system; European model; State planning (socialist) model